EFEKTIVITAS KOMUNIKASI AKUN FACEBOOK @ERJEMEDIA DALAM MENYEBARKAN INFORMASI DAKWAH - Abdi Ihsan; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Facebook is one type of social media that is not only effective if used as one of the communication tool, but also effective if used as a media of online information providers either general information or special information. One of the users who use Facebook as a special media of online information is @erjemedia. An @erjemedia account is a facebook account that provides specific information about dakwah. The theory used in this research is the theory of the effectiveness of communication. The purpose of this study is to find out how much the effectiveness level of communication of facebook account @erjemedia in spreading the information of dakwah.This study uses quantitative research methods, with data collection techniques that is through the spread of questionnaires using google docs by online to followers @erjemedia account with the number of samples is 99 which is determined through random sampling technique. Data analysis techniques in this study using descriptive statistical techniques.The results of this study indicate that the level of the Effectiveness of Communication of Facebook Account @erjemedia As a media that spread the information of dakwah classified as very effective. This is seen from the results of data processing based on six indicators, each indicator reaches 3.70 scale on the receiver indicator, scale of 3.74 on the content indicator, 3.71 scale on the channel of media indicator, 3.66 scale on the format indicator, 3.77 scale on the source code indicator, and 3.62 scale on the timing indicator. So the conclusion obtained by using the average formula of all indicators is 3.7 which is included in a very effective scale range. This shows that facebook account @erjemedia is a very effective media as a media to spread the information of dakwah.